As novas facetas e a ameaça da gripe aviária no mundo globalizado - Granato, Celso Francisco Hernandes [UNIFESP] (2007)
Influenza, or as it is best known, flu, is an acute respiratory infection caused by a virus that affects many different animal species from felines to birds, including humans.Ten years ago, initialy in Hong Kong and after that in Holand and Canada, outbreaks of avian flu have been increasingly reported in human beings. The question is innevitable: are we in the surge of a new flu pandemic like the one we had in 1918? The perspective is even worse now that we have five times the world population and the international travels are no longer made in slow-going ships but instead in super fast jet planes. For us, laboratory professionals, the question of the laboratory diagnosis is crucial. Considering that so many different viruses are associated with respiratory infections and therapeutic measures depend on this definition, this subject assumes an even greater interest.